Pemberdayaan Pengrajin Songket Buleleng - I Made Pradana Adiputra; Nala Hari Wardana (Ilin Institute, 2020)
This community service activity aims to increase the production of songket with the effective use of the cag-cag loom as a traditional tool which until now cannot be replaced as a songket-producing tool because of the anatomical guidelines of the craftsmen's body in working and can produce songket fabrics of good quality. Community service activities are the formation of a joint business group as the basis for the formation of a songket cooperative, the development of designs for North Balinese songket motifs, natural coloring from plant materials from flowers, fruits, roots and plant skins and the effectiveness of using the traditional cag-cag tool. Through the method of socialization, training and mentoring of Jinengdalem Village songket craftsmen, targets and outcomes are generated, namely: the formation of a joint business group, natural coloring of silk threads as the basic material for songket, songket productivity with cag-cag looms and more diversified motif designs according to specific characteristics. North Bali (Buleleng).